(untitled) (Jurnal Ilmiah METANSI ”Manajemen dan Akuntansi”, 2023)
This research aims to determine the influence of two X variables, namely Return On Equity (X1) and Gross Profit Margin (X2) on Profit Growth (Y) on the Indonesian Stock Exchange with 30 samples from 6 Sharia Commercial Banks. This research uses a type of research using panel data. This research is a causal type of research with a quantitative approach. The data analysis method used is multiple linear regression with SPSS 26 software. The t-test results of the Return On Equity (X1) variable show t-test > ttable, namely 4.906 > 2.050 with a sig value of 0.000 < 0.05, it can be concluded that Ha1 is accepted and Ha0 is rejected. From the results of the t-test for the Gross Profit Margin (X2) variable, it shows tcount > ttable, namely 0.254 < 2.050 with a sig value of 0.801 > 0.05, it can be concluded that Ha2 is rejected and Ha0 is accepted. The test results obtained at Sharia Commercial Banks show that there is a significant influence of the independent variables simultaneously on the dependent variable, so Ha3 is accepted, namely that there is a positive and significant influence of the Return On Equity and Gross Profit Margin variables on Profit Growth.